Exploring Personal Financial Management Behaviour Among Generation Z in the Digital Financial Ecosystem : A Qualitative Study - Ghama Haritz Pahlevie (Manajemen Multitalenta Indonesia, 2026)
This research examines the financial management practices of Generation Z in the context of the digital financial age. The quick rise of financial technology has changed how people handle money. It has made things easier, but it has also made things harder for some people. We used a qualitative phenomenological technique to learn about people's lived experiences. We acquired data by doing in-depth interviews with ten people between the ages of 18 and 25 who regularly use digital financial services. The data were looked at utilizing theme analysis. The results show that technology, lifestyle, financial knowledge, and psychological factors like Fear of Missing Out (FoMO) and self-efficacy all affect how people handle their money. Fintech makes things easier to get at, but it also makes people spend money quickly and think about their finances in the short term. Limited financial literacy exacerbates inefficient financial decision-making. This study emphasizes the necessity of enhancing financial literacy and advocating for the proper utilization of financial technologies to facilitate improved financial management within Generation Z.